PENGARUH KOMPRES HANGAT TERHADAP INTENSITAS NYERI PERSALINAN KALA 1 FASE AKTIF PADA IBU BERSALIN DI RUANG KEBIDANAN RSUD RAJA AHMAD TABIB TANJUNGPINANG - Fitriati, Ely; Yunita, Prasida; Susanti, Susanti; Fahnawal, T. Marzila (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
A labor process describes one of pain intensity feeling from the low to stronger one. Based on the medical record data of Raja Ahmad Tabib Regional Public Hospital, the number of deliveries in 2020 was 253 maternity mothers. Meanwhile, ANC (Antenatal Care) visit data from November to December for pregnant women in the third trimester were 30 pregnant women. The purpose of the study was to find out the effect of warm compress on labor pain intensity during first stage of active phase on maternity women at obstetrics room of Raja Ahmad Tabib Regional Public Hospital of Tanjungpinang in 2020. This study used a pre experimental design with one pre-test-post-test group. It was conducted at obstetrics room of Raja Ahmad Tabib Regional Public Hospital of Tanjungpinang on December 2020 to January 2021. The population of this study was 30 respondents that taken by using accidental sampling. Based on the result of the study, the pain intensity of respondents before applying warm compress was moderate pain as many as 4,63 with standart deviation as 1,847 and after applying warm compress was moderate pain as many as 3,17 with standart deviation 1,621 After being given warm compress, statistical test results using t-test showed p value = 0.000 (p > α (0.05), therefore it can be concluded that there was an effect of warm compress on labor pain intensity during first stage of active phase on maternity women at obstetrics room of Raja Ahmad Tabib Regional Public Hospital of Tanjungpinang.